Winter emissions of carbon dioxide, methane and nitrous oxide from a minerotrophic fen under nature conservation management in north-east Germany - V. Huth; G. Jurasinski; S. Glatzel (Mires and Peat, 2012)
Drained peatlands are known to be important sources of carbon dioxide (CO2) and nitrous oxide (N2O). While CO2 emissions occur mainly during the growing season, large N2O emissions may occur during the non-growing season as well. Peatland re-wetting may be an effective measure to prevent those emissions. However, recent research shows that re-wetted peatlands may release large amounts of methane (CH4) during the years immediately after re-wetting whereas abandonment of intensive grassland on drained peat soils possibly leads to low nutrient supply and thus to small greenhouse gas (GHG) emissions. Here we examine the role of extensification practices (such as abandonment of mineral fertilisation, reduced cutting frequency and a cattle-free winter period) on GHG emissions from a temperate peatland during winter. From November 2009 to March 2010 GHG measurements were made on a minerotrophic fen five years after intensive grassland use was abandoned. During the measurement period CO2 and N2O emissions amounted to 4.4 t ha-1 and 2.6 t ha-1 CO2-equivalent, whilst CH4 emissions were negligible. Altogether the site emitted 7 t ha-1 CO2-equivalent, of which 37 % was N2O, even though the winter 2009/2010 was extraordinarily cold. Thus, extensification of grassland use alone may not be sufficient to reduce GHG emissions from temperate peatlands.